Biology-oriented synthesis of benzopyrano[3, 4-c]pyrrolidines. Issue 12 (15th June 2015) - Potowski, Marco; Golz, Christopher; Strohmann, Carsten; Antonchick, Andrey P.; Waldmann, Herbert
Graphical abstract: Abstract: A natural product inspired synthesis of 6, 6, 5-tricyclic compounds via a silver(I)-catalyzed formal 1, 3-dipolar cycloaddition of coumarins with α-iminoesters was developed. The reaction proceeds in a stepwise reaction course under formation of the trans -substituted diastereomer with respect to the 1, 3-dipole and shows a broad substrate scope.